The Influence of Principal Transformational Leadership on Teacher Performance - Nizam, Zain; Rahman, Rashid; Wei, Sun (International Journal of Educational Narratives, 2025)
Background. Service learning has gained recognition as a valuable pedagogical approach in higher education, aiming to bridge the gap between academic theory and real-world practice. In the context of educational institutions, the role of leadership, particularly transformational leadership, plays a significant role in shaping the effectiveness of such programs. Purpose. This research explores the influence of principal transformational leadership on teacher performance within the framework of service learning in higher education institutions. Method. The study aims to assess how transformational leadership behaviors of school principals impact the engagement and performance of teachers involved in service learning programs. Using a quantitative research design, this study surveyed 150 teachers across several higher education institutions that implement service learning programs. Data were collected through questionnaires that assessed principals’ leadership styles and teachers’ performance in service learning contexts. Results. The results indicate that transformational leadership has a positive and significant effect on teacher performance, particularly in areas related to motivation, professional development, and commitment to service learning objectives. Teachers reported higher levels of engagement and effectiveness when their principals exhibited transformational leadership behaviors, such as inspirational motivation, individualized consideration, and intellectual stimulation. Conclusion. This study concludes that principals who embrace transformational leadership can significantly enhance teacher performance, thereby strengthening the impact of service learning programs.